Chebyshev technique in the numerical solution of Delay Differential Equations (Journal of the College of Basic Education, 2022)
We investigate the stability of a numerical solution of the delay differential equation by using explicit Runge-kutta method, when the delay has been approximated by using Chebyshev polynomial instead of using Lagrange and Hirmate interpellation polynomials.